PENGARUH ETIKA BISNIS TERHADAP KEPUASAN PELANGGAN RUMAH MAKAN BEBEK H. SLAMET CABANG JOGLO, JAKARTA BARAT - Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
Consumer satisfaction for a product is very influential on the sustainability of a business, for that it is necessary to maintain the quality of products and services continuously. This study aims to determine whether there is an effect on the application of business ethics to customer satisfaction. The main object of this research is the customers of Bebek H. Slamet in Joglo branch, West Jakarta. The sampling technique uses accidental sampling. The data analysis technique uses multiple linear regression. Does the application of business ethics have a positive and significant effect on the satisfaction of Bebek H. Slamet customers in Joglo branch, West Jakarta. Trust is the most dominant variable of the business ethics variable that affects customer satisfaction at Bebek H. Slamet stalls in Joglo branch, West Jakarta